Guidance on risk assessment of nanomaterials to be applied in the food and feed chain: human and animal health. (3rd August 2021) - ,; More, Simon; Bampidis, Vasileios; Benford, Diane; Bragard, Claude; Halldorsson, Thorhallur; Hernández‐Jerez, Antonio; Hougaard Bennekou, Susanne; Koutsoumanis, Kostas; Lambré, Claude; Machera, Kyriaki; Naegeli, Hanspeter; et al.
Abstract: The EFSA has updated the Guidance on risk assessment of the application of nanoscience and nanotechnologies in the food and feed chain, human and animal health. It covers the application areas within EFSA's remit, including novel foods, food contact materials, food/feed additives and pesticides. The updated guidance, now Scientific Committee Guidance on nano risk assessment (SC Guidance on Nano‐RA), has taken account of relevant scientific studies that provide insights to physico‐chemical properties, exposure assessment and hazard characterisation of nanomaterials and areas of applicability. Together with the accompanying Guidance on Technical requirements for regulated food and feed product applications to establish the presence of small particles including nanoparticles (Guidance on Particle‐TR), the SC Guidance on Nano‐RA specifically elaborates on physico‐chemical characterisation, key parameters that should be measured, methods and techniques that can be used for characterisation of nanomaterials and their determination in complex matrices. The SC Guidance on Nano‐RA also details aspects relating to exposure assessment and hazard identification and characterisation. In particular, nanospecific considerations relating to in vitro/in vivo toxicological studies are discussed and a tiered framework for toxicological testing is outlined. Furthermore, in vitro degradation, toxicokinetics, genotoxicity, local and systemic toxicity as well as general issues relating to testing of nanomaterials are described. Depending on the initial tier results, additional studies may be needed to investigate reproductive and developmental toxicity, chronic toxicity and carcinogenicity, immunotoxicity and allergenicity, neurotoxicity, effects on gut microbiome and endocrine activity. The possible use of read‐across to fill data gaps as well as the potential use of integrated testing strategies and the knowledge of modes or mechanisms of action are also discussed. The Guidance proposes approaches to risk characterisation and uncertainty analysis. Abstract : This publication is linked to the following EFSA Journal article: http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2021.6769/full This publication is linked to the following EFSA Supporting Publications articles: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2021.EN-6502/full, http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2020.EN-1948/full